Engineering safer-by-design, transparent, silica-coated ZnO nanorods with reduced DNA damage potential - Sotiriou, Georgios A. (2014)
Zinc oxide (ZnO) nanoparticles absorb UV light efficiently while remaining transparent in the visible light spectrum rendering them attractive in cosmetics and polymer films. Their broad use, however, raises concerns regarding potential environmental health risks and it has been shown that ZnO nanoparticles can induce significant DNA damage and cytotoxicity. Even though research on ZnO nanoparticle synthesis has made great progress, efforts on developing safer ZnO nanoparticles that maintain their inherent optoelectronic properties while exhibiting minimal toxicity are limited. Here, a safer-by-design concept was pursued by hermetically encapsulating ZnO nanorods in a biologically inert, nanothin amorphous SiO(2) coating during their gas-phase synthesis. It is demonstrated that the SiO(2) nanothin layer hermetically encapsulates the core ZnO nanorods without altering their optoelectronic properties. Furthermore, the effect of SiO(2) on the toxicological profile of the core ZnO nanorods was assessed using the Nano-Cometchip assay by monitoring DNA damage at a cellular level using human lymphoblastoid cells (TK6). Results indicate significantly lower DNA damage (>3 times) for the SiO(2)-coated ZnO nanorods compared to uncoated ones. Such an industry-relevant, scalable, safer-by-design formulation of nanostructured materials can liberate their employment in nano-enabled products and minimize risks to the environment and human health.